EFFECT OF ANGIOTENSIN RECEPTOR BLOCKADE ON ENDOTHELIAL FUNCTION: FOCUS ON OLMESARTAN MEDOXOMIL - C. Ferrario (Российский кардиологический журнал, 2010)
Endothelial dysfunction is the common link between cardiovascular disease risk factors and the earliest event in the cascade of incidents that results in target organ damage. Angiotensin II, the terminal pressor effector arm of the renin-angiotensin-aldosterone system, increases blood pressure (BP) by vasoconstriction and sodium and fluid retention, and has a prooxidative action that induces endothelial dysfunction and contributes to vascular remodeling. Angiotensin receptor blockers (ARBs) reduce BP and morbidity and mortality in patients with hypertension, ventricular hypertrophy, diabetes mellitus, and renal disease. Olmesartan medoxomil is a long-acting, well-tolerated, effective ARB that prevents or reverses endothelial dysfunction in animal models of atherosclerosis, hypertension, diabetes, nephropathy, and retinopathy. Olmesartan medoxomil, a prodrug of olmesartan approved for the treatment of hypertension, has been shown to ameliorate endothelial dysfunction in patients with hypertension or diabetes. In randomized studies, the drug reduces vascular inflammation and the volume of large atherosclerotic plaques, increases the number of regenerative endothelial progenitor cells in the peripheral circulation, improves endotheliumdependent relaxation, and restores the normal resistance vessel morphology. Importantly, the impact of olmesartan medoxomil on endothelial dysfunction is thought to be independent of BP lowering.